Using G6PD tests to enable the safe treatment of Plasmodium vivax infections with primaquine on the Thailand-Myanmar border: A cost-effectiveness analysis - Devine, A; Parmiter, M; Chu, C; Bancone, G; Nosten, F; Price, R; Lubell, Y; Yeung, S (Public Library of Science, 2017)
BACKGROUND: Primaquine is the only licensed antimalarial for the radical cure of Plasmodium vivax infections. Many countries, however, do not administer primaquine due to fear of hemolysis in those with glucose-6-phosphate dehydrogenase (G6PD) deficiency. In other settings, primaquine is given without G6PD testing, putting patients at risk of hemolysis. New rapid diagnostic tests (RDTs) offer the opportunity to screen for G6PD deficiency prior to treatment with primaquine. Here we assessed the cost-effectiveness of using G6PD RDTs on the Thailand-Myanmar border and provide the model as an online tool for use in other settings. METHODS/PRINCIPAL FINDINGS: Decision tree models for the management of P. vivax malaria evaluated the costs and disability-adjusted life-years (DALYs) associated with recurrences and primaquine-induced hemolysis from a health care provider perspective. Screening with G6PD RDTs before primaquine use was compared to (1) giving chloroquine alone and (2) giving primaquine without screening. Data were taken from a recent study on the impact of primaquine on P. vivax recurrences and a literature review. Compared to the use of chloroquine alone, the screening strategy had similar costs while averting 0.026 and 0.024 DALYs per primary infection in males and females respectively. Compared to primaquine administered without screening, the screening strategy provided modest cost savings while averting 0.011 and 0.004 DALYs in males and females respectively. The probabilistic sensitivity analyses resulted in a greater than 75% certainty that the screening strategy was cost-effective at a willingness to pay threshold of US$500, which is well below the common benchmark of per capita gross domestic product for Myanmar. CONCLUSIONS/SIGNIFICANCE: In this setting G6PD RDTs could avert DALYs by reducing recurrences and reducing hemolytic risk in G6PD deficient patients at low costs or cost savings. The model results are limited by the paucity of data available in the literature for some parameter values, including the mortality rates for both primaquine-induced hemolysis and P. vivax. The online model provides an opportunity to use different parameter estimates to examine the validity of these findings in other settings.